Model Model Pendampingan Sosial KPM PKH dalam Rangka Pencapaian Graduasi Mandiri Sejahtera Di Jawa Tengah: Model Pendampingan Sosial KPM PKH dalam Rangka Pencapaian Graduasi Mandiri Sejahtera Di Jawa Tengah - Hastin (Jurnal Ilmu Pekerjaan Sosial, 2024)
Abstract: Independent Graduation is one of aims of Family Hope Program. The Province of Jawa Tengah has been receiving it’s program at ten years, since 2011 until 2021. Refer to independent graduation, Jawa Tengah Province at 2020 named by the Ministry of Social as the highest number of graduation of beneficiaries. According to the data for the last 4 year: at 2017, it was 18.997 beneficiaries (2%), at 2018 it was 9.321 beneficiaries (0.06%), at 2019 it was 14.718 beneficiaries (0.09%), and at 2020 it was 82.296 beneficiaries (5.4%). However, when it measured by manual books, the figure is still small than the target. Therefore, research about model of social assistance and the impact to independent graduation is needed. It’s a quantitative research with survey as design, with 2.885 respondent from 5.069 population of field assistors. With convenience as sampling. Independent variables: (i) years of experience in job, (ii) years of program beneficiaries, (iii) home-visit intensity, (iv) networking with external organization, and (v) mastering knowledge and skill of social assistance. Dependent variable is independent graduation of beneficiaries of PKH. Result is more than 50% respondence said that graduating is most difficult processes. That’s no standard operational about intensities for home-visit. There’re minimal 25% of beneficiaries can be graduated as independent graduation at recent year. And there’s no same form about networking was done by field assistors with beneficiaries. Correlational test shows us that there’re a close relation between intensity of home-visit and graduating processes.